Human nasal olfactory deposition of inhaled nanoparticles at low to moderate breathing rate. (November 2017) - Tian, Lin; Shang, Yidan; Dong, Jingliang; Inthavong, Kiao; Tu, Jiyuan
Abstract: Olfactory pathway, susceptible for direct translocation of inhaled nanoparticles into the brain, has been verified in a number of animal studies over past decades. In case of toxic substances, the extremely low dose strongly suggests a subclinical condition that prevents noticeable neurodegeneration until years after prolonged exposure. The exact mechanism, between elevated presence of toxic substances (e.g. heavy metals) and deteriorated neurofunction in human central nervous system, is still not clear; however, nasal olfactory, being portal of the entry for such a transport route, is undoubtedly a critical junction where hint to the time course and dose dependency might be inferred. Using a physiologically realistic nasal and upper airway replica, this study performed human inhalation simulations of nanoparticles (1–100 nm) under low to moderate breathing conditions (5–14 L/min). Emphasis is on olfactory deposition and the various factors contributing to the process. Details on airflow pattern and particle flux in nasal and olfactory were made visible through a 2D unwrapped surface mapping technique, and it was found out that airflow pattern, especially nasal wall shear had a remarkable correlation to particle movement and deposition at the ultrafine scale (< 1–2 nm). Olfactory deposition efficiency was found to be extremely low (< 3.5%), and showed distinctive variation in high diffusivity region when compared to that in the entire nasal cavity. The entrance profile of olfactory deposited particles was seen to be highly selective and unanimously originated from upper section of the nostril near nasal septum. Current study is of significant value to the understanding of human uptake of inhaled nanoparticles through olfactory pathway. Highlights: Human olfactory deposition of inhaled nanoparticles is computational simulated. Airflow and particle flux to olfactory deposition was visualized and discussed. Distinctive deposition variations were identified in olfactory and nasal cavity. Unique entrance profile for olfactory deposited particles was revealed.